2006
DOI: 10.1007/s00392-006-0414-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnose und Therapie der Sepsis

Abstract: A recent survey conducted by the publicly funded Competence Network Sepsis (Sep- Net) reveals that severe sepsis and/or septic shock occurs in 75,000 inhabitants (110 out of 100,000) and sepsis in 79,000 inhabitants (116 out of 100,000) in Germany annually. This illness is responsible for approx. 60,000 deaths and ranges as the third most frequent cause of death after acute myocardial infarction. Direct costs for the intensive care of patients with severe sepsis alone amount to approx. 1.77 billion euros, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 302 publications
1
2
0
1
Order By: Relevance
“…systemic inflammation, endothelial activation, impaired vasoregulation and intravascular volume depletion [12, 5154]. In the present study, we demonstrate that mild hypothermia increases contractility in failing human myocardium.…”
Section: Discussionsupporting
confidence: 62%
“…systemic inflammation, endothelial activation, impaired vasoregulation and intravascular volume depletion [12, 5154]. In the present study, we demonstrate that mild hypothermia increases contractility in failing human myocardium.…”
Section: Discussionsupporting
confidence: 62%
“…We found that miR-let-7b expression was significantly decreased in septic mice compared with sham treated mice (p<0.0001, Figure 4A ). Sepsis is a kind of severe inflammatory host response diagnosed with inflammatory variables like leukocytosis (WBC counts above 12,000/μL) or leukopenia (WBC counts below 4,000/μL) ( 43 45 ). The more severe the septic inflammation, the closer the disease to sepsis shock, the lower the WBC level.…”
Section: Resultsmentioning
confidence: 99%
“…In Germany, for example, sepsis is the third most common cause of death after cardial infarction and neoplasms. 1 The treatment of sepsis is difficult and needs an interdisciplinary approach. Early diagnosis is necessary to slow the progression of organ dysfunction and improve the patient outcome.…”
Section: Introductionmentioning
confidence: 99%